Influence of kinesiological means on the motor fitness of 15-16 years-old skiers-racers - Golovko, D. E.; Zagrevskaya, A. I.; Shilko, T. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the effect of kinesiological means on the motor fitness of 15-16-year-old ski racers. Methods and structure of the study. The following methods were used in the scientific experiment: analysis of literary sources according to the methodology of organizing the training process of cross-country skiers, testing of motor fitness, pedagogical experiment, methods of mathematical statistics. Experimental work was carried out on the basis of the Children's and Youth Sports School No. 1 of the Tomsk region of the Tomsk region. The study involved 120 skiers aged 15-16, of which experimental and control groups were formed, 60 girls in each group. Results and conclusions. In the course of the study, a block of tools was developed, which includes four kinesiology modules of various target orientations: preparatory and warm-up, basic (load), basic (shortened), warm-up and competitive. Each of these modules solved specific goals and objectives, depending on the period of preparation. As a result of the study, a significant increase in the results of motor fitness of female athletes of the experimental group was recorded, which indicates the effectiveness of the proposed means.